ANALISIS KANDUNGAN LIMBAH INDUSTRI TAHU DAN TEMPE RAHAYU DI KELURAHAN UNER KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Febrian Sayow; Bobby Vian Jhon Polii; Wenny Tilaar; Kojoh Deanne Augustine (Sam Ratulangi University, 2020)
This study aims to (1). Knowing the content and quality of Rahayu's tofu and tempe factory liquidwaste in Uner Village, Kawangkoan Sub-district, Minahasa Regency, and (2). To find out whether Rahayu's tofu and tempe factory liquid waste has exceeded the quality standard. This research was conducted for 3 months, namely in January 2020- March 2020. Sampling locations were carried out in the factory of Tahu and Tempe Rahayu Sub-district in Uner Village, Kawangkoan District, then continued with the analysis at the Manado Industrial Research and Standardization Laboratory (Baristand). This research was a descriptive research and laboratory analysis. Waste water sampling was carried out using a composite sampling method. Sampling was done in the first two places, raw water is used to make tofu and tempe in an inlet and the first was taken from the tofu factory wastewater and tempe in the sewer. Waste liquid sampling was carried out 3 times and for analysis carried out at the Baristand Laboratory to obtain data according to the parameters set in this study. The results showed that the quality of Rahayu tofu and tempe industrial liquid waste based on the analysis of BOD, COD, and TSS parameters that have been analyzed accordingly and have not passed the quality standards set by the Government. However, for the pH parameters are not appropriate and in accordance with the quality standards set by Government.*eprm*